EDUCATIONAL TOURISM AS THE MOST PROFITABLE TYPE OF THE TOURISM INDUSTRY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article analyzes the impact of educational tourism on the global and national economy. Developed countries of the world achieve economic and scientific development by attracting foreign students. Foreign students make a significant contribution to the national economy through tuition fees, living expenses, the service sector and the labor market. They also contribute to increasing the international competitiveness of educational institutions and innovative development. The current state of Uzbekistan in educational tourism is analyzed and ways to increase economic benefits by increasing the flow of foreign students are proposed. The article highlights the international experience of educational tourism and strategic recommendations for Uzbekistan. The opportunities for additional income to the country's economy, improving infrastructure and becoming an international education center are discussed through the development of educational tourism.